E-government adoption among businesses in Jordan - Al-Zoubi, Mohammad Issa; Thi, Lip Sam; Lim, Hock Eam; Al-Zoubi, Saleem (2010)
It is widely acknowledged that electronic government presents a significant opportunity for businesses to compete alongside larger enterprises. For businesses in the developing world in particular, the opportunities afforded be e-government for competing in a global marketplace, are also attractive. However, it has also been observed that e-government poses a considerable challenge for businesses, particularly with regarded to the decisions that must be made about which of the available egovernment application to adopt and to integrated into existing business operations. Hence, the issue of e-government in businesses attracts considerable research works in this area. This conceptual paper reports on the extensive review of prior studies pertaining to the e-government adoption among businesses.